1998
DOI: 10.1046/j.1432-1327.1998.2570178.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an N‐hydroxyguanidine reducing activity of xanthine oxidase

Abstract: A guanoxabenz [1-(2,6-dichlorobenzylideneamino)-3-hydroxyguanidine; an N-hydroxyguanidine] reducing enzymatic activity of rat spleen cytosol was investigated. By means of protein purification and N-terminal amino acid sequencing, the reducing activity was shown to reside in xanthine oxidase. The action of the enzyme on guanoxabenz resulted in the formation of guanabenz [1-(2,6-dichlorobenzylideneamino)-3-guanidine]; the product formation could be monitored by HPLC and its identity was confirmed by NMR analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 29 publications
(26 reference statements)
0
10
0
1
Order By: Relevance
“…In a previous study we showed that the hydroxyguanidine guanoxabenz was capable of supporting the oxidation of xanthine to uric acid both during anaerobic and aerobic conditions (Dambrova et al ., 1998). In subsequent studies we synthesized a novel series of hydroxyguanidines and found that PR5 showed a higher capacity than guanoxabenz to support the anaerobic oxidation of xanthine by xanthine oxidase (Dambrova et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study we showed that the hydroxyguanidine guanoxabenz was capable of supporting the oxidation of xanthine to uric acid both during anaerobic and aerobic conditions (Dambrova et al ., 1998). In subsequent studies we synthesized a novel series of hydroxyguanidines and found that PR5 showed a higher capacity than guanoxabenz to support the anaerobic oxidation of xanthine by xanthine oxidase (Dambrova et al .…”
Section: Discussionmentioning
confidence: 99%
“…In the present study we have evaluated a new possibility to protect the heart in ischaemia and reperfusion. The approach originates from our recent finding that an N‐hydroxyguanidine, guanoxabenz (1‐(2,6‐dichlorobenzylideneamino)‐3‐hydroxyguanidine), an α 2 ‐adrenoceptor active antihypertensive drug (Ledoux et al ., 1981), could also act as an alternative electron acceptor in xanthine oxidase catalyzed oxidation of xanthine (Dambrova et al ., 1998). In the continuation of these studies we synthesized a novel series of N‐hydroxyguanidines and evaluated their capacity to function as electron acceptors in bovine milk xanthine oxidase catalyzed oxidation of xanthine.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study we even purified the spleen cytosolic guanoxabenz converting activity to homogeneity and showed it to reside in xanthine oxidase (Dambrova et al 1998b). The data of fig.…”
Section: Discussionmentioning
confidence: 97%
“…In our previous studies we showed that the guanoxabenz activating mechanism in the spleen was potently inhibited by the xanthine oxidoreductase inhibitor, allopurinol (Mas-sey et al 1970), and we suggested that the activation is mediated by xanthine oxidase (Uhlen et al 1998;Dambrova et al 1998a). In a recent study we even purified the spleen cytosolic guanoxabenz converting activity to homogeneity and showed it to reside in xanthine oxidase (Dambrova et al 1998b). The data of fig.…”
Section: Discussionmentioning
confidence: 97%
“…The reduction of nitrogen-containing groups like aromatic nitro compounds, hydroxamic acids, oximes, tertiary Noxides, azo compounds, and N-hydroxyguanidines by the molybdenum hydroxylases aldehyde oxidase and xanthine oxidase have been described previously (Dambrova et al, 1998;Kitamura et al, 2006). However, the activities were often only described for in vitro investigations under the exclusion of oxygen.…”
Section: Introductionmentioning
confidence: 99%